PENERAPAN METODE BERCERITA DENGAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN KEMAMPUAN EMPATI ANAK USIA DINI - Limarga, Debora Meiliana (IKIP Siliwangi, 2017)
The ability to empathize of the students of group A1 kindergarten of St. Aloysius Bandung is not developed yet, The purpose of this study is to increase the ability to empathize of the kindergarten students through storytelling method with audio-visual media. The ability to empathize must be improved because it is one of social competences in socialization. This study is Class Activity Research Method (Penelitian.Tindakan Kelas, PTK) based on the design of Kemmis & Taggart. Data collection techniques in this research is observation, interview and documentation. Analysis of the data is interactive analysis model. The result of this research shows that after applying storytelling with audio-visual media as the method of teaching to the students, there is an increase in the ability to empathize. In the initial condition (before applying storytelling with audio-visual media as the method of teaching) the ability to empathize of students categorized as â€œunderdevelopedâ€. After applying storytelling with audio-visual media as the method of teaching) the ability to empathize of the students increased and categorized as â€œdeveloped according to expectationsâ€ and growing very wellâ€. Implications of this research showed that application of story-telling method with audio-visual media is effective in improving children's capacity for empathy St. Aloysius TK Group A1 and developing a child's imagination, creating a encouraging learning situation. Researchers recommend that teachers should consistently apply the methods of storytelling with audio-visual media in order to improve students' ability to empathize and create a pleasant classroom atmosphere. Keywords: storytelling with audio-visual media, students's ability to empathize.